2021
DOI: 10.1007/s10741-021-10196-5
|View full text |Cite
|
Sign up to set email alerts
|

New onset nonischemic cardiomyopathy post liver transplantation

Abstract: A new onset acute heart failure (HF) with a sudden drop in the left ventricular ejection fraction (LVEF) post orthotopic liver transplant (LT) is a rare but a potentially fatal complication. Because in most of the cases there is no evidence of coronary thrombosis, it can be classified as nonischemic cardiomyopathy. More specifically, clinical presentation of this syndrome shares many features with stress-induced or takotsubo cardiomyopathy. The known factors that predispose these patients to acute HF during or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Upon encountering environmental stress, such as transplantation, impaired contractility fails to adapt to initial changes. Decreased vascular resistance and increased cardiac output increase cardiac preload, resulting in abnormal filling of the ventricle and blood redistribution (12,13). Histological examination of a heart with CCM revealed edema, cardiomyocyte hypertrophy, nuclear vacuolization, and fibrosis, which occurred in conjunction with enhanced accumulation of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Upon encountering environmental stress, such as transplantation, impaired contractility fails to adapt to initial changes. Decreased vascular resistance and increased cardiac output increase cardiac preload, resulting in abnormal filling of the ventricle and blood redistribution (12,13). Histological examination of a heart with CCM revealed edema, cardiomyocyte hypertrophy, nuclear vacuolization, and fibrosis, which occurred in conjunction with enhanced accumulation of collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, we observed that patients with severe hIRI required a significantly greater cumulative dose of intraoperative inotropic and vasopressor medications. Pressor use is an established risk factor for development of stress-induced cardiomyopathy, which is a known post-LT cardiac complication that has significant impact on recipient mortality [ 10 , 15 20 ]. It is also hypothesized that cirrhotic cardiomyopathy can be responsible for post-LT cardiac dysfunction [ 10 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of nonischemic HF was stress-induced Takotsubo cardiomyopathy (11/24), sepsis (8/24), and other causes (5/24; see Supplementary File 1, SDC, http://links.lww.com/TXD/A538 for details). Compared to sepsis-induced cardiomyopathy, the median time for the onset of stress-induced HF was significantly shorter (31 [15-104] versus 4 [3][4][5][6] d, respectively; χ 2 = 11, P < 0.001). Complete, partial, and no recovery of heart function was recorded in 14-6-4 of 24 patients, respectively.…”
Section: Nonischemic Hfmentioning
confidence: 99%
“…Regrettably, 2 decades of research into the diagnostic, therapeutic, and preventive strategies of post-LT myocardial dysfunction have provided scant data regarding its etiology, characteristics, and prognosis. 6,7 Thus, there remains a dire need to fill this knowledge gap so that the loss of both lives and grafts can be minimized.…”
mentioning
confidence: 99%